Use of the Dublin Core Standard to Express Open Metadata Related to Software Engineering Experiments - Santana, Filipe Amadeu; Cordeiro, André F. R.; OliveiraJr, Edson (Anais do Workshop de Práticas de Ciência Aberta para Engenharia de Software (OpenScienSE); 2023: Anais do III Workshop de Práticas de Ciência Aberta para Engenharia de Software, 2023)
Metadata represents descriptive information about data. They facilitate data retrieval and ensure data interoperability. Metadata can be expressed with metadata standards. In this study, we investigated using metadata standards to express metadata of Software Engineering (SE) Experiments. We compared five different standards. The Dublin Core Standard presented better results based on the documentation criteria, automated processing, and the possibility of application in an SE experimentation context. We provide examples of how to use Dublin Core. In a future study, a tool will be developed to perform metadata specifications in Dublin Core toward promoting open science practices for SE experiments.